Peningkatan Kesadaran PHBS Rumah Tangga Melalui Program SEJAGAT (Sejam Jaga Kesehatan dan Kebersihan Tepat) Sebagai Upaya Preventif Penyakit Diare di Wilayah Pemukiman RW 13 Kelurahan Cipedes - Laferani, Yuni; Azahra, Amelia; Hidayah, Hana Humaira; Nurrobbani, Naila; Batubara, Angelica Kezya Mutiara Sesa; Awalyah, Tika Iswandari; Oktaviani, Gita Suci (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Diarrhea cases are still one of the significant environmental health problems in Cipedes Village, Tasikmalaya City. Based on data from the Cipedes Health Center in 2024, there were 513 cases of diarrhea, exceeding the annual target set. The low practice of Clean and Healthy Living Behavior (PHBS) in households is the main factor causing the high number. The SEJAGAT (Sejam Jaga Kebersihan dan Kesehatan Tepat) program is designed as an educational intervention to increase awareness and practice of PHBS in the community. This study uses a quantitative and qualitative descriptive approach with data collection techniques through questionnaires and field observations of 264 heads of families or wives who represent them. The results of the study showed that most people have access to clean water and toilet facilities, but there are still shortcomings in terms of knowledge about the steps for washing hands with soap, making oralit, and the importance of health education. The implementation of the SEJAGAT program was able to improve PHBS practices such as washing hands, maintaining food hygiene, and drinking water treatment, thus contributing to efforts to reduce the incidence of diarrhea in the area.